Looking toward tomorrow: Exploring the dynamics of future anxiety in the community life of people living with HIV - Ika Wahyuningrum; Niken Titi Pratitis (University of Merdeka Malang, 2026)
Living with HIV requires not only long-term management of physical health but also affects how individuals view their future. For people living with HIV (PLHIV), the future is often seen as uncertain and sometimes threatening, with ongoing concerns about survival, relationships, and social roles. In this context, this study aims to explore the psychological dynamics of future-oriented anxiety in the everyday lives of PLHIV communities. The study employed a mixed-methods approach with a qualitative-dominant, exploratory sequential design. Primary data were collected through community observation, in-depth interviews, and Focus Group Discussions (FGDs), and were subsequently enriched by quantitative screening using the Future Anxiety Scale (FAS) as a supportive tool for mapping dimensions of future-related anxiety. Thematic analysis was conducted with the assistance of NVivo software to systematically identify patterns and thematic structures. The findings indicate that future anxiety is a dominant and relatively persistent psychological experience, ranging from negative expectations about the future to observable effects on emotions, physical responses, and everyday behavior. Four main themes were identified: perceiving the future as a domain of threat, a sense of lack of control over life direction, the dominance of negative future imagery accompanied by emotional distress, and impacts on daily functioning and social roles. In addition, the study reveals the ambivalent role of the community, which simultaneously functions as a protective factor and as a source of collective anxiety through ongoing social interactions. These findings underscore that future anxiety cannot be understood solely as an individual concern, but rather as a psychosocial experience shaped within a community context. This study contributes conceptually to HIV and mental health research by positioning future orientation as a critical lens for understanding the psychological well-being of PLHIV.